2012
DOI: 10.5560/znb.2012-0122
|View full text |Cite
|
Sign up to set email alerts
|

Nitroimidazoles Part 7. Synthesis and Anti-HIV Activity of New 4-Nitroimidazole Derivatives

Abstract: Reverse transcriptase enzyme (RT) is an attractive target for the development of new drugs useful in AIDS therapy and HIV non-nucleoside reverse transcriptase inhibitors (NNRTIs), and offers the possibility of generating structures of increased potency. On this basis, a series of 4-oxo-3-phenyl-2-(phenylimino)thiazolidin-5-ylidene, 3-hydroxypropyl, 3-azidopropyl, and 3-aminopropyl derivatives of 1-benzyl-2-ethyl-4-nitroimidazoles 6-8, as well as the substituted 1,2,3-triazolo analogs 12-14, the diazepam 15 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…A perusal of the literature revealed that pyrimidine derivatives and the uracil and thymine nitrogen bases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] are efficient inhibitors to protect steel in acidic solutions [ 15 , 17 ]. 1,2,3-Triazoles have been the subject of considerable research, mainly due to their usefulness in synthetic organic chemistry and also due to their variety of interesting biological activities, forming part of the scaffolds of antibacterial and antituberculosis agents [ 18 , 19 ], neuraminidase inhibitors [ 20 ], anticancer compounds [ 21 , 22 , 23 , 24 ], antiviral agents [ 25 , 26 , 27 ], analgesic compounds [ 28 ], fungicidal activity [ 29 , 30 , 31 ], protein tyrosine phosphatase inhibitors [ 32 , 33 ], and assorted biomolecules (nucleosides and nucleotides) [ 34 , 35 ]. On the other hand, 1,2,3-triazoles have other applications, like in chemosensors [ 36 ] and organocatalysts [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A perusal of the literature revealed that pyrimidine derivatives and the uracil and thymine nitrogen bases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] are efficient inhibitors to protect steel in acidic solutions [ 15 , 17 ]. 1,2,3-Triazoles have been the subject of considerable research, mainly due to their usefulness in synthetic organic chemistry and also due to their variety of interesting biological activities, forming part of the scaffolds of antibacterial and antituberculosis agents [ 18 , 19 ], neuraminidase inhibitors [ 20 ], anticancer compounds [ 21 , 22 , 23 , 24 ], antiviral agents [ 25 , 26 , 27 ], analgesic compounds [ 28 ], fungicidal activity [ 29 , 30 , 31 ], protein tyrosine phosphatase inhibitors [ 32 , 33 ], and assorted biomolecules (nucleosides and nucleotides) [ 34 , 35 ]. On the other hand, 1,2,3-triazoles have other applications, like in chemosensors [ 36 ] and organocatalysts [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, other teams were interested in the synthesis of derivatives having a 1,3‐diazepine moiety, as potential HIV protease inhibitors, but these showed only weak activity 113,114 …”
Section: 3‐diazepine Derivatives As Enzyme Inhibitorsmentioning
confidence: 99%
“…Based on the imidazole pharmacological importance of imidazole derivatives and in contituation of our previous work on imidazole analogues with their antiviral and anticancer activity, [22][23][24][25][26][27][28][29] we report here new derivatives of nitroimidazole-containing piperazine derivatives and evaluation of their anticancer activity as well as the molecular docking study.…”
Section: Introductionmentioning
confidence: 95%